Orientation for adults in a changing society. - Porcaro, Emilio (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The Centres for Adult Education (CPIA) play a key role in the Adult Education system. They not only help to increase education levels among the adult population but also support the integration of individuals with non-Italian citizenship. Additionally, CPIA helps develop basic and transversal skills necessary to exercise the right to citizenship. This article, based on theoretical perspectives and experiences from CPIA, aims to explore the theme of guidance in adult classes. Guidance is a cross-cutting practice that fosters the development of skills needed to consciously exercise rights to citizenship in an ever-changing society.